Worlds apart? The nature and quality of the educational experiences of pupils with a statement for special educational needs in mainstream primary schools. (21st April 2014) - Webster, Rob; Blatchford, Peter
<x xml:space="preserve">Abstract</x> Findings from the Deployment and Impact of Support Staff (DISS) project showed that support from teaching assistants (TAs) had a strong negative impact on the academic progress of pupils, and this applied particularly to pupils with a statement of special educational needs (SEN). Although the DISS project found that such pupils experienced less contact with teachers, little is known about school‐ and classroom‐level decision‐making relating to provision. This paper addresses the nature and quality of the educational experiences of pupils with statements, and who has responsibility for putting in place and delivering provision for these pupils within schools. Results come from the Making a Statement (MAST) project, which tracked the educational experiences of 48 9‐ and 10‐year‐old pupils with the highest level of SEN, attending mainstream primary schools in England. The study involved the thematic analysis of 48 detailed pupil case studies, drawing on interview, documentation and field note data. Results are presented in terms of four key themes: (1) the explicit and subtle forms of separation these pupils experience daily; (2) the high level of pedagogical decision‐making TAs have for pupils with statements; (3) the impoverished pedagogical diet pupils with statements receive, compared to their peers; and (4) the gaps in teachers' and TAs' knowledge concerning meeting the needs of pupils with statements. The findings have particular implications for the deployment of TAs and for provision for pupils with SEN, with and without statements.